Origin and implications of the low-Fe igneous series at Buldir Island, western Aleutian arc - Gene M. Yogodzinski; Shawn Arndt; Ryan Waldman; Michael Bizimis; Jeffrey Vervoort; Kenneth W. W. Sims (Contributions to Mineralogy and Petrology, 2026)
Volcanic whole-rock compositions from Buldir Island define a highly calc-alkaline (low-Fe) igneous series, with molar Mg/Mg + Fe* (total iron Mg#) mostly > 0.60; SiO 2 from 50–64 wt.%; and distinctly low FeO*, CaO, CaO/Al 2 O 3 , and FeO*/Al 2 O 3 relative to MgO. Many Buldir samples have trace element characteristics similar to western Aleutian seafloor lavas along upward curving trends of increasing Sr and Sr/Y with increasing SiO 2 and decreasing MgO. Least radiogenic Sr in andesites only (57–62 wt.% SiO 2 with 87 Sr/ 86 Sr ~ 0.7029) requires a key role for source mixing in the origin of the low-Fe series at Buldir. Andesites and dacites falling outside these source mixing trends show evidence of fractional crystallization interpreted to be a late-stage (over-printing) effect. Partitioning data indicate that heavy REEs will behave compatibly in amphibole-saturated melts evolving at temperatures < 1000 °C. However, recent hydrous and high fO 2 experiments show that Buldir melts with more than 4–5 wt.% MgO were unlikely to have reached amphibole saturation and cannot explain the decline in Yb concentrations starting at >9 wt.% MgO. Distinctive reverse sigmoidal (backward-S) REE pattern shapes in Buldir samples are also unlikely to be products of amphibole removal from evolving liquids and are instead interpreted to reflect melting of a light REE-depleted MORB source under eclogite conditions followed by interaction of the resulting hydrous-felsic slab melt with mantle peridotite upon ascent. Published pMELTS simulations and experimental observations indicate this style of melt-rock reaction will also create low FeO* and CaO in primitive (high-Mg#) melts over a wide range of SiO 2 and MgO, as observed in Buldir and western Aleutian seafloor datasets. The implication is that distinctive aspects of low-Fe calc-alkalinity in most Buldir samples with SiO 2 from 50 to 62% are created at sub-MOHO depths where cool-hydrous-siliceous partial melts of subducted-eclogitized MORB rise, decompress, and undergo thermal-chemical exchange with depleted peridotite that is hotter by hundreds of °C.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Shallow-level differentiation of phonolitic lavas from Sumaco Volcano, Ecuador - Jennifer M. Garrison; Kenneth W. W. Sims; Gene M. Yogodzinski; Ricardo D. Escobar; Sean Scott; Patricia Mothes; Minard L. Hall; Patricio Ramon (Contributions to Mineralogy and Petrology, 2018)

Timescales of storage and recycling of crystal mush at Krafla Volcano, Iceland - Kari M. Cooper; Kenneth W. W. Sims; John M. Eiler; Neil Banerjee (Contributions to Mineralogy and Petrology, 2016)

The effect of CO2 on the measurement of 220Rn and 222Rn with instruments utilising electrostatic precipitation - Derek Lane-Smith; Kenneth W. W. Sims (Acta Geophysica, 2013)